2010
DOI: 10.1097/opx.0b013e3181d1d954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Examiner Experience and Technique on the Alternate Cover Test

Abstract: Purpose To compare the repeatability of the alternate cover test between experienced and inexperienced examiners and the effects of dissociation time and examiner bias. Methods Two sites each had an experienced examiner train 10 subjects (inexperienced examiners) to perform short and long dissociation time alternate cover test protocols at near. Each site conducted testing sessions with an examiner triad (experienced examiner and two inexperienced examiners) who were masked to each other’s results. Each tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 8 publications
2
32
0
Order By: Relevance
“…1,2,8,10,11 Holmes et al 1 reported inter-examiner variability of the APCT in adults with sixth nerve palsy and suggested a change in measurements of 10 PD or more was suggestive 96 Â standard deviation of the difference) to be ±4.9 PD for near fixation and ±4.6 PD for distance fixation. The solid line shows the mean of the differences to be À0.16 vs À0.14 PD for near and distance fixation, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…1,2,8,10,11 Holmes et al 1 reported inter-examiner variability of the APCT in adults with sixth nerve palsy and suggested a change in measurements of 10 PD or more was suggestive 96 Â standard deviation of the difference) to be ±4.9 PD for near fixation and ±4.6 PD for distance fixation. The solid line shows the mean of the differences to be À0.16 vs À0.14 PD for near and distance fixation, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Deviations, based on the fixation of preference, were recorded as the value of the prism that reached the first neutral endpoint. To ensure full dissociation, the cover paddle was held as closely as possible to the patient's eye in combination with the ''long dissociation protocol'' of Anderson et al 2 The cover paddle was initially held in front of the non-dominant eye for 5 seconds. ''The eye was alternately occluded for a count of 2 seconds for nine additional excursions of the cover paddle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations